Characteristics of Waste Plastics Pyrolytic Oil and Its Applications as Alternative Fuel on Four Cylinder Diesel Engines - Nosal Nugroho Pratama; Harwin Saptoadi (International Journal of Renewable Energy Development, 2014)
Waste plastics recycling using pyrolysis method is not only able to decrease a number of environment pollutant but also able to produce economical and high quality hydrocarbon products. Two experiments were conducted to completely study Waste Plastic Pyrolytic Oil (WPPO) characteristics and its applications.  First experiment investigated oil characteristics derived from pyrolysis process in two stages batch reactors: pyrolysis and catalytic reforming reactor, at maximum temperature 500oC and 450oC respectively. Waste Polyethylene (PE), Polypropylene (PP), Polystyrene (PS), Polyethylene Terepthalate (PET) and others were used as raw material. Nitrogen flow rate at 0.8 l/minutes was used to increase oil weight percentage. Indonesian natural zeolite was used as catalyst. Then, second experiment was carried out on Diesel Engine Test Bed (DETB) used blending of WPPO and Biodiesel fuel with a volume ratio of 1:9. This experiment was specifically conducted to study how much potency of blending of WPPO and biodiesel in diesel engine. The result of first experiment showed that the highest weight percentage of WPPO derived from mixture of PE waste (50%wt), PP waste (40%wt) and PS waste (10%wt) is 45.13%wt. The more weight percentage of PE in feedstock effected on the less weight percentage of WPPO, the more percentage of C12-C20 content in WPPO and the higher calorific value of WPPO. Characteristics of WPPO such as, Specific Gravity, Flash point, Pour Point, Kinematic Viscosity, Calorific value and percentage of C12-C20 showed interesting result that WPPO could be developed as alternative fuel on diesel fuel blending due to the proximity of their characteristics. Performance of diesel engine using blending of WPPO and biodiesel on second experiment gave good result so the WPPO will have great potency to be valuable alternative liquid fuel in future, especially on stationary diesel engine and transportation engine application.